1993
DOI: 10.1093/occmed/43.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Tinnitus in noise-exposed workers

Abstract: Tinnitus is said to be a common complaint of workers who are exposed to noise. We studied the prevalence and characteristics of tinnitus in 647 noise-exposed workers who had been notified as cases of noise-induced deafness. One hundred and fifty-one had tinnitus, giving a prevalence of 23.3 per cent. The tinnitus was bilateral in 42.4 per cent of cases, and of high frequency in 44.4 per cent. In 23.8 per cent it was associated with other symptoms. About 30 per cent of those with tinnitus complained that it int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(35 citation statements)
references
References 0 publications
4
30
1
Order By: Relevance
“…This is in agreement with other studies in other types of groups (work or general population) ( 12 ). Moreover, impulse noise during leisure time was another risk factor for tinnitus in pilots, which is in agreement with other studies ( 15,17 ). The strong positive association between tinnitus and annoyance due to noise in the cockpit showed that the noise level in the cockpit is suffi cient to cause disturbance in pilots suffering from tinnitus.…”
Section: Tinnitus Risk In Pilots -Lindgrensupporting
confidence: 91%
“…This is in agreement with other studies in other types of groups (work or general population) ( 12 ). Moreover, impulse noise during leisure time was another risk factor for tinnitus in pilots, which is in agreement with other studies ( 15,17 ). The strong positive association between tinnitus and annoyance due to noise in the cockpit showed that the noise level in the cockpit is suffi cient to cause disturbance in pilots suffering from tinnitus.…”
Section: Tinnitus Risk In Pilots -Lindgrensupporting
confidence: 91%
“…Moreover, Phoon et al (1993) found that noise-exposed workers with tinnitus had higher average hearing thresholds than those without tinnitus, whereas we found that subjects without tinnitus had more overall hearing loss than subjects with tinnitus. These discrepancies could be due to a diVerent choice of subjects and a diVerent inclusion criterion for tinnitus.…”
Section: Discussioncontrasting
confidence: 57%
“…The average age (29 years) of the studied population is lower than that of the literature, which ranged between 40 and 50 years 1,16,[22][23] . Various studies suggest hearing status is an important factor associated with tinnitus prevalence in individuals exposed to noise 8,11,[24][25][26] . The author 8 concluded that 33% of the individuals with NIHL had tinnitus, whereas prevalence rates in groups of people with other hearing disorders and normal hearing were of 9.7% and 20% respectively.…”
Section: Discussionmentioning
confidence: 99%